Mating Populations of Fusarium Section Liseola from Rice, Sugarcane and Maize - Latiffah Zakaria,; Heng Mei Hsuan ,; Baharuddin Salleh, (Tropical Life Sciences Research, 2011)
Mating studies were conducted on 78 isolates of Fusarium species section Liseola from rice, sugarcane and maize. From the crosses with tester strains of Gibberella fujikuroi species complex, 64.1% (50 out of 78 isolates) were cross-fertile with tester strains of mating populations A to E. The results of the mating studies showed that of the 50 isolates, 19 belonged to mating population A (Gibberella moniliformis), 18 to mating population B (Gibberella sacchari), 4 to mating population E (Gibberella subglutinans), 6 to mating population D (Gibberella intermedia) and 3 to mating population C (G. fujikuroi). Identification of several mating populations from rice, sugarcane and maize could be important biological entities under field conditions. Kajian pengawanan telah dijalankan ke atas 78 pencilan spesies Fusarium seksyen Liseola yang telah dipencilkan daripada padi, tebu dan jagung. Berdasarkan ujian persilangan dengan strain penguji spesies kompleks Gibberella fujikuroi, 64.1% (50 daripada 78 pencilan) berjaya mengacuk-subur dengan strain penguji populasi kacukan A hingga E. Keputusan daripada kajian pengawanan ini menunjukkan daripada 50 pencilan yang mengawan, 19 termasuk dalam populasi kacukan A (Gibberella moniliformis), 18 dalam populasi kacukan B (Gibberella sacchari), 4 dalam populasi kacukan E (Gibberella subglutinans), 6 dalam populasi kacukan D (Gibberella intermedia) and 3 dalam populasi kacukan C (G. fujikuroi). Pengenalpastian beberapa populasi kacukan pada padi, tebu dan jagung boleh dianggap sebagai entiti biologi penting di lapangan.